Empowering Communities: Blynk Software Training and Prototyping for Environmental Monitoring Around Grape Plants - Fahmy Rinanda Saputri; Angga Permana; Melissa Indah Fianty; Wirawan Istiono; Alexander Waworuntu (I-Com: Indonesian Community Journal, 2024)
This community engagement paper highlights a training initiative on Blynk software and prototype development for environmental monitoring around grape plants. The training took place in a vineyard in the Tangerang Selatan region. The majority of participants expressed satisfaction with the program, citing increased ease in grape plant observations. The use of Blynk software, coupled with IoT functionality, enabled seamless smartphone monitoring, providing participants with a convenient and efficient means of tracking and observing grape plants. This initiative not only empowered the local community with valuable technological skills but also enhanced their ability to monitor and manage grape cultivation effectively. The integration of Blynk and IoT technology proved to be a practical solution for community-based environmental observation, promoting sustainable agricultural practices in the grape cultivation sector. The Blynk software training and prototyping for grape plant environmental monitoring in Tangerang, supported by faculty and student teams, proceeded smoothly. Participants' reported ease levels after the training were: 40% very easy, 40% easy, and 20% difficult.